Presystolic mitral closure sound in aortic regurgitation with left ventricular hypertrophy and first degree heart block. Issue 1 (July 1982) - Traill, T A; Fortuin, N J
Abstract : We report a patient who developed aortic regurgitation and first degree atrioventricular block caused by infective endocarditis complicating aortic valve stenosis. There was premature closure of the mitral valve and, in the absence of an Austin Flint murmur, a simultaneous high frequency sound was audible which we regard as a presystolic first heart sound. That such a sound may be associated with valve closure, even though this precedes electrical and mechanical ventricular systole, provides further support for the valvular origin of the first heart sound.